2020
DOI: 10.3390/cells9092126
|View full text |Cite
|
Sign up to set email alerts
|

FRET-Based Sorting of Live Cells Reveals Shifted Balance between PLK1 and CDK1 Activities During Checkpoint Recovery

Abstract: Cells recovering from the G2/M DNA damage checkpoint rely more on Aurora A-PLK1 signaling than cells progressing through an unperturbed G2 phase, but the reason for this discrepancy is not known. Here, we devised a method based on a FRET reporter for PLK1 activity to sort cells in distinct populations within G2 phase. We employed mass spectroscopy to characterize changes in protein levels through an unperturbed G2 phase and validated that ATAD2 levels decrease in a proteasome-dependent manner. Comparing unpert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
2
0
0
Order By: Relevance
“…By implementing DNA damage in G2 via manipulation of the Cdk1 activation threshold, we found that cells enter M phase with higher CycB-Cdk1 levels after DNA damage in G2 phase. This is in line with recently published experimental results [ 95 ]. Whether the subsequent M phase takes longer than in unperturbed cells, as is predicted by the model, was not assessed in the cited study.…”
Section: Discussionsupporting
confidence: 94%
“…By implementing DNA damage in G2 via manipulation of the Cdk1 activation threshold, we found that cells enter M phase with higher CycB-Cdk1 levels after DNA damage in G2 phase. This is in line with recently published experimental results [ 95 ]. Whether the subsequent M phase takes longer than in unperturbed cells, as is predicted by the model, was not assessed in the cited study.…”
Section: Discussionsupporting
confidence: 94%
“…By implementing DNA damage in G2 via manipulation of the Cdk1 activation threshold, we found that cells enter M-phase with higher CycB-Cdk1 levels after DNA damage in G2 phase. This is in line with recently published experimental results [88]. Whether the subsequent M-phase takes longer than in unperturbed cells, as is predicted by the model, was not assessed in the cited study.…”
Section: Discussionsupporting
confidence: 83%